Promotion Program and Repurchase Intention : The Mediation Role of Customer Trust in The IM3 Salatiga Outlet - Setiani, Dinda Nova; Firdaus, Firdaus; Nurhayati, Nurhayati; Jumai , Jumai (Economics and Business International Conference Proceeding, 2024)
This research aims to analyze the influence of sales promotions on repurchase intentions at the IM3 Salatiga outlet, taking into account trust. The population in this research is the IM3 Outlet in the Salatiga area with a sample of 109 respondents, who will later be analyzed using the Structural Equation Model - Partial Least Squares (SEM-PLS) method. The analysis results show that sales promotions have a significant positive influence on repurchase intentions, both directly and through increasing customer trust in IM3 products. These findings indicate that effective promotional communications can build customer trust, which in turn increases the likelihood of customers to repurchase the product. In this research, it is important for telecommunications companies such as IM3 to optimize promotional strategies to maintain and increase customer loyalty amidst intense market competition. Thus, this research contributes to understanding the factors that influence consumers’ repurchase intentions, as well as their relevance in the context of marketing and strategic management.